Research on the Transmissibility of Wire Rope Insulators as Damping Equipment on the RX 200 Rocket Payload - Djatmiko, Agus Budi; Ediwan, Ediwan; Ronald, Ronald; Putra, Gunawan (Indonesian Journal of Aerospace, 2021)
Wire rope insulator or steel wire rope insulator has applications for vibration isolation in equipment and structures in many industrial machinery. Steel wire rope insulators can also be used as suitable equipment to dampen vibrations in rocket loads. The disturbance acceleration as the excitation caused by the combustion process on the rocket can cause a vibration with a large amplitude which results in damage to the rocket's payload structure and the electronic equipment on the rocket's payload cannot work as desired. Based on the experience of electronic equipment, it will be damaged if the disturbance acceleration of 3 g acting on the rocket is not reduced, for this reason a vibration damping device is designed, the apparatus consists of several stainless steel wire ropes tied between two parallel binders arranged in such a way as to provides a damping effect on the rocket's payload. A wire rope insulator consists of several stainless steel wire ropes tied between two parallel straps. One application of this type of wire rope insulator is to isolate the vibrations that occur in the rocket, so that it does not interfere with the performance of the electronic equipment on the rocket's payload. Electronic equipment is used to determine the position of the rocket and its stability. In this study, the wire rope material used is stainless steel with syield = 350 e+6 N / m2 with a diameter of d = 3 mm. The research objective of the vibratory damper of wire rope insulators was to determine the magnitude of the transmissibility of the ruffler during and after resonance. Transmissibility (TR) is the ratio of the force transmitted to the disturbing or excitation force. The results of the research on a damper with a disturbance acceleration of 3 g at resonance, obtained the transmissibility value (TR) = 2.54, the spring stiffness k = 200537.3 N/m and the damping coefficient c = 331.5 N/m/sec, then after conditions Â obtained transmissibility (TR) <1 This shows that the damper with steel wire isolator is good enough to dampen vibrations in the RX 200 rocket payload.